No-motor impairment in patients with Parkinson’s disease - I. A. Zhukova; N. G. Zhukova; V. M. Alifirova (Бюллетень сибирской медицины)
No-motor symptoms, vesting patients with Parkinson’s disease (PD), predominate at clinical finding of PD. The aim of research was analysis of no-motor disorders against gender the patients with PD. The results of this study have shown that there are not any differences in the age, the age of onset of disease and illness duration between the genders. We have found that the trembling form of PD, cognitive and anxious disorders appear more often of female then male.